Faktor yang Mempengaruhi Minat Generasi Milenial dalam Menggunakan Produk Asuransi Syari’ah - Syaputri, Windi Aprillian; Siti nur izzati; Arini, Zesxia Viviola (Syar'Insurance: Jurnal Asuransi Syariah, 2024)
Sharia insurance is one of the sharia financial products chosen by the public, especially the millennial generation who are Muslim. This is because there is awareness regarding insurance that does not contain usury, gharar and maisir, so sharia insurance is chosen because it is guided by sharia principles. Basically, the millennial generation in Bengkalis is interested in using sharia insurance products. However, there are many reasons why this desire is not realized, one of which is because the number of sharia insurance agents or companies in Bengkalis is very small. This research was conducted using descriptive qualitative methods with data collection tools in the form of interviews and literature studies. The research results show that the millennial generation, especially those who adhere to the Islamic religion, are interested in using sharia insurance products. However, in Bengkalis it is still very rare to find sharia insurance companies or agents so that the desire of the millennial generation to use sharia insurance cannot be realized optimally. There are several factors that can influence the millennial generation's interest in using sharia insurance, including religiosity (religion), promotional factors, social factors, personal factors, financial literacy factors, and income factors. The author also provides advice to the parties concerned, especially on Bengkalis Island, to provide outreach to the millennial generation regarding sharia insurance products and expand the target market by increasing the number of sharia insurance companies or agents to accommodate the interests of the millennial generation in Bengkalis towards sharia insurance products.